Resin carbon microspheres with anticoagulation effect as well as preparation method and application of resin carbon microspheres
By covalently grafting poly(vinyltriethoxysilane/acrylic acid) on the surface of resin carbon microspheres, the problem of poor blood compatibility of blood perfusion adsorbents is solved, and efficient anticoagulation and adsorption performance is achieved, with clinical Application potential.
Patent Information
- Application Number
- CN202411505764.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-03
AI Technical Summary
The existing blood perfusion adsorbents have problems such as poor blood compatibility and easy to cause side effects, and are difficult to effectively use in clinical applications.
By covalently grafting poly(vinyl triethoxysilane/acrylic acid) on the surface of hydroxylated resin carbon microspheres, a resin carbon microsphere adsorbent with good anticoagulation effect is formed, thereby improving the anticoagulation and adsorption of the material. performance.
It significantly improves the hemocompatibility and anticoagulant properties of the adsorbent, enhances the adsorption ability of small and medium-sized toxins in the blood, and reduces production costs, and has potential clinical application prospects.
Smart Images

Figure CN119236897A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of blood perfusion adsorbents, and in particular relates to a surface modification method of resin carbon microspheres and an application thereof in the field of biomedical materials. Background Art
[0002] Hemoperfusion is a blood purification method with low treatment cost, wide application range and great development potential. Various blood purification therapies including hemoperfusion have been included in the treatment guidelines of many countries to remove inflammatory mediators and block cytokine storm in critically ill patients. However, as the core of hemoperfusion technology, hemoperfusion adsorbents generally have problems such as poor blood compatibility, inability to contact with blood cells, and easy to cause side effects. Therefore, in response to the above problems, a simple, efficient and universal surface modification method is designed and developed, which takes into account the requirements of blood compatibility and adsorption performance of hemoperfusion adsorbents, which is of great significance to the clinical application and development of hemoperfusion adsorbents.
[0003] Resin materials are a class of synthetic cross-linked porous polymers, including anion / cation exchange resins and neutral adsorption resins, and are often used as adsorbents in blood perfusion. Resin adsorbents have the characteristics of high mechanical strength, good blood compatibility, adjustable pore size structure and specific surface area, and can selectively adsorb harmful toxins in the blood. The application of resin adsorbents began with ion exchange resins (J.Lab.Clin.Med., 1948, 33, 841.). Since they carry ionizable groups, they can selectively adsorb charged molecules in the blood. However, ion exchange resins can seriously affect the pH value and electrolyte balance of the blood (Clin.Toxicol., 1980, 17, 493.), and are limited in actual application. Adsorption resins use the polar and non-polar groups on their surfaces to remove toxins, and can be used in the treatment of diseases such as uremia and critical liver disease. Although the application of adsorption resin in the medical field started relatively late (New Engl. J. Med., 1971, 284, 874.), its effective adsorption of medium and large molecules and protein-bound toxins such as β2-microglobulin and bilirubin laid a good foundation for the subsequent development of new perfusion adsorbents.
[0004] At present, more and more researchers are focusing on developing new blood perfusion adsorbents with excellent performance. Li et al. used polycarboxylate betaine (PCB) hydrogel to coat polystyrene resin (H103) microparticles to develop a new type of PCB-H103 adsorbent. This adsorbent can not only effectively adsorb middle molecules and protein-bound toxins, but also solve the problem of poor blood compatibility of resin materials (J.Colloid Interf.Sci., 2019, 555, 145.). Liu et al. used acrylonitrile / divinylbenzene cross-linked copolymer microspheres as raw materials and prepared nitrogen-containing porous carbon adsorbents (NPCA) with good biosafety by pyrolysis for the removal of protein-bound uremic toxins (PBUTs). The results showed that the removal effect of NPCA microspheres on PBUTs was significantly higher than that of commonly used commercial adsorbents, and had certain clinical application prospects (Mat.Sci.Eng.C-Mater., 2021, 121, 111879.). Qin et al. added hydroxyethyl methacrylate (HEMA) and acrylic acid (AA) to PES solution, and an in-situ cross-linking polymerization reaction was performed to prepare a PES-HEMA-AA membrane with good blood compatibility. The modified PES-HEMA-AA membrane has significantly improved hydrophilicity, antifouling and blood compatibility, especially in the improvement of blood anticoagulation performance, and has application potential in the field of blood purification (J. Membrane Sci., 2014, 468: 172-183.). Yu et al. prepared a phosphatidylethanolamine-polyacrylic acid modified poly (vinyl alcohol-co-triallyl isocyanurate) (PVA@PAA-PE) adsorbent using free radical suspension polymerization and covalent grafting. This adsorbent can not only effectively remove low-density lipoprotein, total cholesterol and triglycerides, but also maintain the level of anti-atherosclerotic high-density lipoprotein in the blood of patients with hyperlipidemia. It is a potential dual-functional adsorbent for the treatment of hyperlipidemia (J.Mater.Chem.B, 2021, 9, 6364.). CN113600148A discloses a blood perfusion adsorbent based on heparin-modified chitosan / cellulose microspheres, which has good mechanical strength and stability, so as to better meet the needs of blood perfusion for the mechanical strength of the blood perfusion adsorbent. The rich amino groups contained in the chitosan molecules make the adsorbent rich in positive charge, which can efficiently remove negatively charged endotoxins; the heparin coating on the outer layer of the adsorbent can form a complex with histones, thereby quickly removing histones from the blood. CN114904489A discloses a blood perfusion adsorbent for removing uric acid and a preparation method thereof. The blood perfusion adsorbent is mainly composed of agarose gel microspheres, and montmorillonite is embedded in the agarose microspheres.The prepared blood perfusion adsorbent is cheap and easy to obtain, has high adsorbent capacity, good biocompatibility, and is suitable for whole blood perfusion treatment of hyperuricemia. The adsorption rate of uric acid in the blood is as high as 23% to 41%, which can greatly reduce the uric acid level in the patient's body in a short time, quickly improve the condition, and reduce the occurrence of gout. CN118513014A discloses a bilirubin adsorbent with anticoagulant effect, a preparation method and application. The bilirubin adsorbent is prepared by chemically cross-linking sulfated polysaccharides and styrene-divinylbenzene polymers, and has good bilirubin adsorption effect and good anticoagulant performance.
[0005] In summary, efficient adsorption performance and good blood compatibility are the key factors that determine whether hemoperfusion adsorbents can be used in clinical disease treatment. Therefore, rationally modifying the surface of resin materials and developing hemoperfusion adsorbents with anticoagulant function are important directions for the future development of blood purification. Summary of the invention
[0006] The purpose of the present invention is to provide a resin carbon microsphere adsorbent with good anticoagulant effect, good cell compatibility and high adsorption performance.
[0007] The anticoagulant resin carbon microsphere adsorbent provided by the present invention is prepared by covalently grafting poly(vinyl triethoxysilane / acrylic acid) on the surface of hydroxylated resin carbon microspheres. The poly(vinyl triethoxysilane / acrylic acid) is prepared by initiating a free radical polymerization reaction of vinyl triethoxysilane and acrylic acid in the presence of azobisisobutyronitrile and triethyl phosphate.
[0008] The method for preparing the resin carbon microsphere adsorbent with anticoagulant effect of the present invention is characterized in that the preparation method comprises the following steps:
[0009] Step 1: dissolve vinyl triethoxysilane and acrylic acid in triethyl phosphate, remove oxygen from the reaction system, then add azobisisobutyronitrile, heat and stir under nitrogen protection to carry out polymerization reaction, and after the reaction, dialyze and freeze-dry the reaction solution to obtain poly(vinyl triethoxysilane / acrylic acid).
[0010] Step 2: placing the resin carbon microspheres in a piranha solution and heating and stirring for reaction, and ultrasonically cleaning and drying after the reaction to obtain hydroxylated resin carbon microspheres.
[0011] Step 3: Add hydroxylated resin carbon microspheres and poly (vinyl triethoxysilane / acrylic acid) into deionized water, heat and stir to react, and adjust the pH of the reaction solution to alkaline with 1 mol / L NaOH aqueous solution. After the reaction is completed, solidify, wash and dry to obtain a resin carbon microsphere adsorbent with anticoagulant effect.
[0012] In the above step 1, the volume ratio of the vinyl triethoxysilane to acrylic acid and triethyl phosphate is preferably 0.01-0.03:0.01-0.05:1, and the mass ratio of the total volume of the vinyl triethoxysilane and acrylic acid to the mass of azobisisobutyronitrile is 0.5-1 mL:6-10 mg.
[0013] In the above step 1, the polymerization reaction is preferably carried out by heating and stirring at 60 to 80° C. for 15 to 24 hours under nitrogen protection.
[0014] In the above step 2, the resin carbon microspheres refer to the resin carbon microspheres used in the field of blood perfusion.
[0015] In the above step 2, the resin carbon microspheres are preferably placed in the piranha solution and heated and stirred at 60 to 80° C. for a reaction of 0.5 to 2 h.
[0016] In the above step 3, the mass ratio of the hydroxylated resin carbon microspheres to poly(vinyltriethoxysilane / acrylic acid) is preferably 1:2-5.
[0017] In the above step 3, the reaction is preferably heated and stirred at 45 to 55° C. for 2 to 4 hours, and the pH of the reaction solution is adjusted to 11.0 to 12.0 with a 1 mol / L NaOH aqueous solution.
[0018] In the above step 3, the curing is performed by standing at 65-75° C. for 1-3 hours.
[0019] The present invention also provides the use of the resin carbon microsphere adsorbent with anticoagulant effect as a blood perfusion adsorbent.
[0020] The present invention has the following beneficial effects:
[0021] 1. The present invention first initiates a polymerization reaction by using vinyl triethoxysilane monomers and acrylic acid monomers under an initiator, thereby finally forming poly (vinyl triethoxysilane / acrylic acid) containing carboxylate ions, which have a charge density equivalent to that of heparin and can significantly inhibit the activity of thrombin and factor Xa. Therefore, the introduction of poly (vinyl triethoxysilane / acrylic acid) can improve the anti-coagulation performance of the material.
[0022] 2. The present invention utilizes surface grafting technology to fix poly (vinyl triethoxysilane / acrylic acid) on the surface of resin carbon microspheres, giving the resin carbon microspheres good anticoagulant and adsorption properties, and constructs the material through covalent connection to have excellent long-term stability.
[0023] 3. The vinyl triethoxysilane in the poly (vinyl triethoxysilane / acrylic acid) of the present invention is a kind of silane coupling agent, a low molecular weight organosilicon compound with a special structure, which can react with both the hydroxyl group in the inorganic substance and the organic group in the polymer. The present invention utilizes the characteristics of the silane coupling agent to covalently graft the acrylic polymer with anticoagulant properties on the surface of the substrate, providing a simple and universal strategy for solving the problem of poor blood compatibility of biomaterials, and providing a research basis for realizing efficient and safe blood perfusion adsorbents.
[0024] 4. The present invention significantly improves the blood compatibility and cell compatibility of the obtained adsorbent by covalently grafting poly(vinyl triethoxysilane / acrylic acid) on the surface of hydroxylated resin carbon microspheres, especially enhancing its blood anticoagulant effect, without affecting the adsorption performance of the material for small and medium-molecule toxins in the blood. In addition, poly(vinyl triethoxysilane / acrylic acid) is only grafted on the surface of resin carbon microspheres, which greatly reduces the production cost of blood perfusion adsorbents, has certain market advantages, and has potential application prospects in the field of blood purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the H NMR spectrum of vinyltriethoxysilane, acrylic acid and poly(vinyltriethoxysilane / acrylic acid).
[0026] Figure 2 This is the full XPS spectrum of the sample before and after modification with resin carbon microspheres.
[0027] Figure 3 It is the high-resolution C1s XPS spectra of the samples before and after modification with resin carbon microspheres.
[0028] Figure 4 It is the scanning electron micrograph of platelet adhesion before and after modification of resin carbon microspheres.
[0029] Figure 5 is the plasma recalcification time before and after modification of resin carbon microspheres.
[0030] Figure 6 It is an analysis of the anti-hemolytic performance of resin carbon microspheres before and after modification.
[0031] Figure 7 This is the cytotoxicity analysis of resin carbon microspheres before and after modification.
[0032] Figure 8 Creatinine and VB before and after modification of resin carbon microspheres 12 and Lysozyme adsorption capacity.
[0033] Fig. 9 is the BSA retention rate before and after modification of resin carbon microspheres. DETAILED DESCRIPTION
[0034] The technical scheme of the present invention is described clearly and completely below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the preferred embodiments of the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, any modification, equivalent replacement, improvement, etc. made by ordinary technicians in the field without creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0035] The resin carbon microspheres used in the following examples were provided by Hillcon Blood Purification Equipment Company.
[0036] Example 1
[0037] Step 1: Dissolve 300 μL of vinyl triethoxysilane (VTES) and 400 μL of acrylic acid (AA) in 10 mL of triethyl phosphate, stir and dissolve until a transparent homogeneous phase is obtained, and then nitrogen is bubbled for 2 h to remove oxygen from the reaction system. Then, 7 mg of azobisisobutyronitrile is added, and the polymerization reaction is carried out at 80° C. for 20 h under nitrogen protection and stirring. After the reaction, the reaction solution is dialyzed in deionized water for 72 h (dialysis bag: 8000-14000 Da), and the reaction solution is vacuum concentrated and freeze-dried to obtain poly (vinyl triethoxysilane / acrylic acid), which is recorded as P (3VTES / 4AA). Figure 1 The following are the H NMR spectra of vinyl triethoxysilane, acrylic acid and poly(vinyl triethoxysilane / acrylic acid). By comparing the spectra of vinyl triethoxysilane and acrylic acid, it can be seen that the peak of poly(vinyl triethoxysilane / acrylic acid) at δ=12.22ppm belongs to the protons in the carboxyl group of the acrylic acid segment, the peak at 3.73ppm belongs to the protons on the methylene group in vinyl triethoxysilane, and the broad peak at 1.40-2.40ppm is caused by the methyl group in the vinyl triethoxysilane molecule and the protons of -CH-CH2- in the polymer main chain. In addition, since the solvent used in the polymerization reaction is triethyl phosphate, which has a high boiling point and is not easy to remove, the peaks corresponding to triethyl phosphate are detected at 4.00ppm and 1.24ppm. By analyzing the chemical shifts of each hydrogen in poly(vinyl triethoxysilane / acrylic acid), the successful polymerization of vinyl triethoxysilane and acrylic acid is proved.
[0038] Step 2: Place 0.5 g of resin carbon microspheres (RC) in 100 mL of piranha solution (a mixture of 98% concentrated H2SO4 and 30% hydrogen peroxide in a volume ratio of 7:3), stir and react at 80°C for 1 hour, then ultrasonically clean the sample alternately with deionized water and anhydrous ethanol for 3 times, each time for 10 minutes; finally, place the cleaned sample in a 50°C oven and dry it for 24 hours to obtain hydroxylated resin carbon microspheres (RC-OH).
[0039] Step 3: 0.4 g of hydroxylated resin carbon microspheres and 1.2 g of poly (vinyl triethoxysilane / acrylic acid) were added to 10 mL of deionized water, stirred at 50 ° C for 2 h, and then the pH of the reaction solution was adjusted to 11.0 with 1 mol / L NaOH aqueous solution, and then the stirring reaction was continued for 1 h to promote the condensation of vinyl triethoxysilane and form a siloxane network. After the reaction, the sample was placed in a 70 ° C oven for curing for 1 h, and then the sample was rinsed with anhydrous ethanol 3 times, and finally placed in a 50 ° C oven for 12 h to obtain resin carbon microspheres with surface covalent grafting poly (vinyl triethoxysilane / acrylic acid) (RC-P (3VTES / 4AA)), that is, a resin carbon microsphere adsorbent with anticoagulant effect.
[0040] Table 1 Surface element composition of samples before and after modification of resin carbon microspheres
[0041]
[0042] As can be seen from Table 1, the surfaces of the original resin carbon microspheres and the resin carbon microspheres treated with piranha solution are composed of C, O, and S elements. The difference is that the C content of the resin carbon microspheres treated with piranha solution is reduced from 91.80% to 86.92%, and the O content is increased from 7.71% to 12.88%. This is because the number of oxygen-containing functional groups on the surface of the resin carbon microspheres increases after being treated with piranha solution, which further shows that the resin carbon microspheres are successfully oxidized by the piranha solution. Figure 2 It can be seen that the XPS full spectrum of the resin carbon microspheres with covalent grafting of poly(vinyltriethoxysilane / acrylic acid) on the surface shows characteristic peaks of Na1s, Si2s, and Si2p compared with the original resin carbon microspheres and the resin carbon microspheres treated with piranha solution. These correspond to the Na element in sodium hydroxide and the Si element contained in the polymer molecules, respectively. In addition, the surface C / O atomic ratio of the resin carbon microspheres with covalent grafting of poly(vinyltriethoxysilane / acrylic acid) on the surface is significantly lower than that of the resin carbon microspheres treated with piranha solution, indicating that poly(vinyltriethoxysilane / acrylic acid) is successfully grafted on the surface of the resin carbon microspheres. Figure 3 (a) is the original resin carbon microsphere, (b) is the resin carbon microsphere treated with piranha solution, and (c) is the resin carbon microsphere with covalent grafting of poly (vinyl triethoxysilane / acrylic acid) on the surface. The C1s high-resolution spectra were separated and fitted, and four sub-peaks were found. The peak at the binding energy of 284.4eV belongs to the C-Si bond, the peak at 284.5eV belongs to the CC bond, the peak at 286.1eV belongs to the CO bond, and the peak at 289.2eV belongs to the OC=O bond. The appearance of the C-Si bond further indicates the successful grafting of the polymer.
[0043] Example 2
[0044] Step 1: Dissolve 100 μL of vinyl triethoxysilane and 500 μL of acrylic acid in 10 mL of triethyl phosphate, stir and dissolve until a transparent homogeneous phase is obtained, and then bubbling with nitrogen for 1.5 h is used to remove oxygen from the reaction system. Then, 6 mg of azobisisobutyronitrile is added, and the polymerization reaction is carried out at 80° C. for 16 h under nitrogen protection and stirring. After the reaction, the reaction solution is dialyzed in deionized water for 72 h (dialysis bag: 8000-14000 Da), and the reaction solution is concentrated in vacuo, and freeze-dried to obtain poly(vinyl triethoxysilane / acrylic acid).
[0045] Step 2: Place 0.5 g of resin carbon microspheres in 100 mL of piranha solution (a mixture of 98% concentrated H2SO4 and 30% hydrogen peroxide in a volume ratio of 7:3), stir the reaction at 80°C for 1 hour, then ultrasonically clean the sample alternately with deionized water and anhydrous ethanol for 3 times, each time for 10 minutes; finally, place the cleaned sample in a 50°C oven and dry it for 24 hours to obtain hydroxylated resin carbon microspheres.
[0046] Step 3: 0.4 g of hydroxylated resin carbon microspheres and 1.2 g of poly (vinyl triethoxysilane / acrylic acid) were added to 10 mL of deionized water, stirred at 50 ° C for 2 h, and then the pH of the reaction solution was adjusted to 11.0 with 1 mol / L NaOH aqueous solution, and then the stirring reaction was continued for 1 h to promote the condensation of vinyl triethoxysilane and form a siloxane network. After the reaction, the sample was placed in a 70 ° C oven for curing for 2 h, and then the sample was rinsed with anhydrous ethanol 3 times, and finally placed in a 50 ° C oven for 12 h to obtain resin carbon microspheres with covalent grafting of poly (vinyl triethoxysilane / acrylic acid) on the surface, that is, resin carbon microsphere adsorbent with anticoagulant effect.
[0047] Example 3
[0048] Step 1: Dissolve 200 μL of vinyl triethoxysilane and 500 μL of acrylic acid in 10 mL of triethyl phosphate, stir and dissolve until a transparent homogeneous phase is obtained, and then bubbling with nitrogen for 1 hour is used to remove oxygen from the reaction system. Then, 7 mg of azobisisobutyronitrile is added, and the polymerization reaction is carried out at 80° C. for 18 hours under nitrogen protection and stirring. After the reaction, the reaction solution is dialyzed in deionized water for 72 hours (dialysis bag: 8000-14000 Da), and the reaction solution is concentrated in vacuo, and freeze-dried to obtain poly(vinyl triethoxysilane / acrylic acid).
[0049] Step 2: Place 0.5 g of resin carbon microspheres in 100 mL of piranha solution (a mixture of 98% concentrated H2SO4 and 30% hydrogen peroxide in a volume ratio of 7:3), stir the reaction at 80°C for 1 hour, then ultrasonically clean the sample alternately with deionized water and anhydrous ethanol for 3 times, each time for 10 minutes; finally, place the cleaned sample in a 50°C oven and dry it for 24 hours to obtain hydroxylated resin carbon microspheres.
[0050] Step 3: 0.4 g of hydroxylated resin carbon microspheres and 1.2 g of poly (vinyl triethoxysilane / acrylic acid) were added to 10 mL of deionized water, stirred at 55 ° C for 1 hour, and the pH of the reaction solution was adjusted to 11.5 with 1 mol / L NaOH aqueous solution, and then the stirring reaction was continued for 1 hour to promote the condensation of vinyl triethoxysilane and form a siloxane network. After the reaction, the sample was placed in a 70 ° C oven for curing for 1 hour, and then the sample was rinsed with anhydrous ethanol 3 times, and finally placed in a 50 ° C oven for 12 hours to obtain resin carbon microspheres with covalent grafting of poly (vinyl triethoxysilane / acrylic acid) on the surface, that is, resin carbon microsphere adsorbent with anticoagulant effect.
[0051] Example 4
[0052] Step 1: Dissolve 300 μL of vinyl triethoxysilane and 500 μL of acrylic acid in 10 mL of triethyl phosphate, stir and dissolve until a transparent homogeneous phase is obtained, and then bubbling with nitrogen for 2 h is used to remove oxygen from the reaction system. Then, 8 mg of azobisisobutyronitrile is added, and the polymerization reaction is carried out at 80° C. for 20 h under nitrogen protection and stirring. After the reaction, the reaction solution is dialyzed in deionized water for 72 h (dialysis bag: 8000-14000 Da), and the reaction solution is concentrated in vacuo, and freeze-dried to obtain poly(vinyl triethoxysilane / acrylic acid).
[0053] Step 2: Place 0.5 g of resin carbon microspheres in 100 mL of piranha solution (a mixture of 98% concentrated H2SO4 and 30% hydrogen peroxide in a volume ratio of 7:3), stir the reaction at 80°C for 1 hour, then ultrasonically clean the sample alternately with deionized water and anhydrous ethanol for 3 times, each time for 10 minutes; finally, place the cleaned sample in a 50°C oven and dry it for 24 hours to obtain hydroxylated resin carbon microspheres.
[0054] Step 3: 0.4 g of hydroxylated resin carbon microspheres and 1.2 g of poly (vinyl triethoxysilane / acrylic acid) were added to 10 mL of deionized water, stirred at 55 ° C for 2 h, and then the pH of the reaction solution was adjusted to 12.0 with 1 mol / L NaOH aqueous solution, and then the stirring reaction was continued for 1 h to promote the condensation of vinyl triethoxysilane and form a siloxane network. After the reaction, the sample was placed in a 70 ° C oven for curing for 2 h, and then the sample was rinsed with anhydrous ethanol 3 times, and finally placed in a 50 ° C oven for 12 h to obtain resin carbon microspheres with covalent grafting of poly (vinyl triethoxysilane / acrylic acid) on the surface, that is, resin carbon microsphere adsorbent with anticoagulant effect.
[0055] Example 5
[0056] Step 1: Dissolve 300 μL of vinyl triethoxysilane and 300 μL of acrylic acid in 10 mL of triethyl phosphate, stir and dissolve until a transparent homogeneous phase is obtained, and then bubbling with nitrogen for 1.5 h is used to remove oxygen from the reaction system. Then, 6 mg of azobisisobutyronitrile is added, and the polymerization reaction is carried out at 80° C. for 24 h under nitrogen protection and stirring. After the reaction, the reaction solution is dialyzed in deionized water for 72 h (dialysis bag: 8000-14000 Da), and the reaction solution is concentrated in vacuo, and freeze-dried to obtain poly(vinyl triethoxysilane / acrylic acid).
[0057] Step 2: Place 0.5 g of resin carbon microspheres in 100 mL of piranha solution (a mixture of 98% concentrated H2SO4 and 30% hydrogen peroxide in a volume ratio of 7:3), stir the reaction at 80°C for 1 hour, then ultrasonically clean the sample alternately with deionized water and anhydrous ethanol for 3 times, each time for 10 minutes; finally, place the cleaned sample in a 50°C oven and dry it for 24 hours to obtain hydroxylated resin carbon microspheres.
[0058] Step 3: Add 0.4g of hydroxylated resin carbon microspheres and 1.2g of poly(vinyl triethoxysilane / acrylic acid) to 10mL of deionized water, stir and react at 45°C for 2h, adjust the pH of the reaction solution to 11.5 with 1mol / L NaOH aqueous solution, and continue to stir and react for 2h to promote the condensation of vinyl triethoxysilane and form a siloxane network. After the reaction is completed, place the sample in a 70°C oven for curing for 1.5h, then rinse the sample 3 times with anhydrous ethanol, and finally place it in a 50°C oven for drying for 12h to obtain resin carbon microspheres with covalent grafting of poly(vinyl triethoxysilane / acrylic acid) on the surface, that is, resin carbon microsphere adsorbent with anticoagulant effect.
[0059] Example 6
[0060] Step 1: Dissolve 300 μL of vinyl triethoxysilane and 500 μL of acrylic acid in 10 mL of triethyl phosphate, stir and dissolve until a transparent homogeneous phase is obtained, and then bubbling with nitrogen for 2.5 h is used to remove oxygen from the reaction system. Then, 8 mg of azobisisobutyronitrile is added, and the polymerization reaction is carried out at 80° C. for 24 h under nitrogen protection and stirring. After the reaction, the reaction solution is dialyzed in deionized water for 72 h (dialysis bag: 8000-14000 Da), and the reaction solution is concentrated in vacuo, and freeze-dried to obtain poly(vinyl triethoxysilane / acrylic acid).
[0061] Step 2: Place 0.5 g of resin carbon microspheres in 100 mL of piranha solution (a mixture of 98% concentrated H2SO4 and 30% hydrogen peroxide in a volume ratio of 7:3), stir the reaction at 80°C for 1 hour, then ultrasonically clean the sample alternately with deionized water and anhydrous ethanol for 3 times, each time for 10 minutes; finally, place the cleaned sample in a 50°C oven and dry it for 24 hours to obtain hydroxylated resin carbon microspheres.
[0062] Step 3: 0.4 g of hydroxylated resin carbon microspheres and 1.2 g of poly (vinyl triethoxysilane / acrylic acid) were added to 10 mL of deionized water, stirred at 55 ° C for 1 hour, and the pH of the reaction solution was adjusted to 12.0 with 1 mol / L NaOH aqueous solution, and then the stirring reaction was continued for 2 hours to promote the condensation of vinyl triethoxysilane and form a siloxane network. After the reaction, the sample was placed in a 70 ° C oven for curing for 2.5 hours, then rinsed with anhydrous ethanol 3 times, and finally placed in a 50 ° C oven for 12 hours to obtain resin carbon microspheres with covalent grafting of poly (vinyl triethoxysilane / acrylic acid) on the surface, that is, resin carbon microsphere adsorbent with anticoagulant effect.
[0063] In order to demonstrate the beneficial effects of the present invention, the performance of the resin carbon microspheres with poly(vinyltriethoxysilane / acrylic acid) covalently grafted on the surface in the above Example 1 was tested as follows:
[0064] 1. Platelet adhesion performance test
[0065] The platelet adhesion experiment was conducted using platelet-rich plasma. Weigh 100 mg of the sample to be tested that has been sterilized at high temperature, place it in a 24-well plate, add 250 μL of platelet-rich plasma to completely immerse the sample, and then incubate it in a 37°C constant temperature and humidity chamber for 1 hour. After the incubation is completed, rinse the sample 3 times with platelet-rich plasma solution to remove non-adherent platelets. The sample was then fixed in a 2.5wt% glutaraldehyde aqueous solution at 4°C for 2 hours, and then dehydrated step by step with ethanol aqueous solutions with volume fractions of 10%, 30%, 50%, 70%, 80%, 90%, and 100%, each time for 10 minutes. After the sample is dry, spray gold on its surface, and observe the number and morphology of platelets adhered to the sample surface using a field emission scanning electron microscope. The results are shown in Figure 2. Figure 4 , where (a) is the original resin carbon microsphere, (b) is the resin carbon microsphere treated with piranha solution, and (c) is the resin carbon microsphere with poly(vinyl triethoxysilane / acrylic acid) covalently grafted on the surface. As can be seen from the figure, compared with the original resin carbon microsphere, the resin carbon microsphere with poly(vinyl triethoxysilane / acrylic acid) covalently grafted on the surface has excellent anti-platelet adhesion performance.
[0066] 2. Plasma recalcification analysis
[0067] The plasma recalcification test is an important indicator for evaluating the intrinsic coagulation system. It refers to the re-addition of Ca to platelet-poor plasma (PPP). 2+ , the time it takes for the intrinsic coagulation process to recover. Figure 5 It can be seen that the plasma recalcification time of the resin carbon microspheres treated with piranha solution increased from 5.5min of the original resin carbon microspheres to 7.5min. This is because its hydrophilicity is better than that of the original resin carbon microspheres, which can delay the activation of coagulation factors. The plasma recalcification time of the resin carbon microspheres with covalently grafted poly (vinyl triethoxysilane / acrylic acid) on the surface is significantly prolonged because the carboxyl groups contained in the polymer can react with Ca in the plasma. 2+ Interact with each other, thereby effectively delaying the activation of the intrinsic coagulation pathway and increasing its anticoagulant activity.
[0068] 3. Analysis of anti-hemolytic performance
[0069] In vitro hemolysis test is a reliable method to evaluate the blood compatibility of biomaterials. 0.9wt% NaCl aqueous solution was selected as the negative control and deionized water as the positive control. Each sample was tested in parallel 3 times. The results are detailed in Figure 6 . Figure 6The hemolysis rates of the original resin carbon microspheres, the resin carbon microspheres treated with piranha solution, and the resin carbon microspheres with covalent grafting of poly(vinyl triethoxysilane / acrylic acid) on the surface are shown. The hemolysis rate of the resin carbon microspheres treated with piranha solution is as high as 23.4%, which is due to the high acidity of the residual piranha solution in the pores, which causes the rupture of red blood cells and then induces hemolysis. After poly(vinyl triethoxysilane / acrylic acid) was introduced on the surface of the resin carbon microspheres treated with piranha solution, the hemolysis rate was significantly reduced to only 2.9%, indicating that poly(vinyl triethoxysilane / acrylic acid) can maintain the integrity of the structure and function of red blood cells and effectively improve the blood compatibility of the adsorbent.
[0070] 4. Cytotoxicity Analysis
[0071] Human umbilical vein endothelial cells were used as model cells. The CCK-8 method was used to determine the cell viability of different resin carbon microsphere samples after co-culture with cells for 24h and 48h to evaluate the cytotoxicity of the samples. The results are shown in Figure 7 . As can be seen from the figure, when the cell culture time is 24h, the original resin carbon microspheres and the resin carbon microspheres treated with piranha solution can significantly inhibit the activity of human umbilical vein endothelial cells, and their survival rates are 66.1% and 61.5% respectively, indicating that the cytotoxicity of the samples is high and is not conducive to cell proliferation and growth. When the surface of the resin carbon microspheres is grafted with poly (vinyl triethoxy silane / acrylic acid), the cell viability of the cultured human umbilical vein endothelial cells is significantly increased, reaching 84.1%, indicating that the sample has no obvious cytotoxicity. After continuing to culture the cells for 24h, the cell survival rate of the sample is close to that of the control group, which is 99.5%. This is because the vinyl triethoxy silane contained in poly (vinyl triethoxy silane / acrylic acid) is non-toxic, can promote cell adhesion, and is beneficial to cell growth. The results show that the resin carbon microspheres with poly (vinyl triethoxy silane / acrylic acid) grafted on the surface have good cell compatibility and can be used as blood contact materials in the field of blood purification.
[0072] 5. Adsorption performance analysis
[0073] In order to comprehensively evaluate the adsorption performance of different resin carbon microspheres, this experiment not only determined the adsorption of small molecule toxins creatinine (Creatinine) and medium molecule toxins vitamin B12 (VB 12 ) and the adsorption capacity of the macromolecular toxin lysozyme (results see Figure 8 ), and the retention rate of bovine serum albumin of the samples was determined by protein retention experiment to explore its effect on human plasma protein. The results are shown in Fig. 9The results showed that although the grafting of poly(vinyltriethoxysilane / acrylic acid) would reduce the adsorption of medium and small molecular toxins by resin carbon microspheres, it could adsorb more positively charged toxins while reducing the loss of albumin because it provided a large amount of negative charges to the surface of the material.
Claims
1. A resin carbon microsphere adsorbent with anticoagulant effect, characterized in that: The resin carbon microsphere adsorbent is prepared by covalently grafting poly(vinyl triethoxysilane / acrylic acid) on the surface of hydroxylated resin carbon microspheres.
2. The anticoagulant resin carbon microsphere adsorbent according to claim 1, characterized in that: The poly(vinyl triethoxysilane / acrylic acid) is prepared by initiating a free radical polymerization reaction of vinyl triethoxysilane and acrylic acid in the presence of azobisisobutyronitrile and triethyl phosphate.
3. A method for preparing the anticoagulant resin carbon microsphere adsorbent according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: dissolving vinyl triethoxysilane and acrylic acid in triethyl phosphate, removing oxygen from the reaction system, then adding azobisisobutyronitrile, heating and stirring under nitrogen protection to carry out polymerization reaction, and after the reaction is completed, dialyzing and freeze-drying the reaction solution to obtain poly(vinyl triethoxysilane / acrylic acid); Step 2: placing the resin carbon microspheres in a piranha solution and heating and stirring to react, and ultrasonically cleaning and drying after the reaction to obtain hydroxylated resin carbon microspheres; Step 3: Add hydroxylated resin carbon microspheres and poly (vinyl triethoxysilane / acrylic acid) into deionized water, heat and stir to react, and adjust the pH of the reaction solution to alkaline with 1 mol / L NaOH aqueous solution. After the reaction is completed, solidify, wash and dry to obtain a resin carbon microsphere adsorbent with anticoagulant effect.
4. The method for preparing the anticoagulant resin carbon microsphere adsorbent according to claim 3, characterized in that: In step 1, the volume ratio of the vinyl triethoxysilane to acrylic acid and triethyl phosphate is 0.01-0.03:0.01-0.05:1, and the mass ratio of the total volume of the vinyl triethoxysilane and acrylic acid to the mass of azobisisobutyronitrile is 0.5-1 mL:6-10 mg.
5. The method for preparing the anticoagulant resin carbon microsphere adsorbent according to claim 3, characterized in that: In step 1, the polymerization reaction is carried out by heating and stirring at 60-80° C. for 15-24 hours under nitrogen protection.
6. The method for preparing the anticoagulant resin carbon microsphere adsorbent according to claim 3, characterized in that: In step 2, the resin carbon microspheres are placed in the piranha solution and heated and stirred at 60 to 80° C. for a reaction of 0.5 to 2 h.
7. The method for preparing the anticoagulant resin carbon microsphere adsorbent according to claim 3, characterized in that: In step 3, the mass ratio of the hydroxylated resin carbon microspheres to poly(vinyltriethoxysilane / acrylic acid) is 1:2-5.
8. The method for preparing the anticoagulant resin carbon microsphere adsorbent according to claim 3, characterized in that: In step 3, the reaction is heated and stirred at 45-55° C. for 2-4 h, and the pH of the reaction solution is adjusted to 11.0-12.0 with a 1 mol / L NaOH aqueous solution.
9. The method for preparing the anticoagulant resin carbon microsphere adsorbent according to claim 3, characterized in that: In step 3, the curing is performed by standing at 65-75° C. for 1-3 hours.
10. Use of the anticoagulant resin carbon microsphere adsorbent according to claim 1 as a blood perfusion adsorbent.